Answer:
A) find its center = (3, 2)
B) find the radius of the circle = √104
C) find the equation of the circle = x² + y² - 6x - 4y -91 = 0
Explanation:
A)- The center must be the mid-points of (-2, 1) and (8, 3).
So, using the equation of mid-point,
![h=(x_(1)+x_(2))/(2) and k=(y_(1)+y_(2))/(2)](https://img.qammunity.org/2020/formulas/mathematics/college/dr27j3sgi0nk627biblo4c2tg8td199uj5.png)
Here, (x₁, y₁) = (-2, 1) and (x₂, y₂) = (8, 3)
Putting these value in above equation. We get,
h = 3 and k = 2
Thus, Center = (h, k) = (3, 2)
B)- For finding the radius we have to find the distance between center and any of the end point.
Thus using Distance Formula,
![Distance=\sqrt{(x_(2)-x_(1))^(2)+(y_(2)-y_(1))^(2)}](https://img.qammunity.org/2020/formulas/mathematics/college/ay0ymaoddqpnj6mdc1y5424ybtn26gikj3.png)
![Radius =\sqrt{(8+2)^(2)+(3-1)^(2)}](https://img.qammunity.org/2020/formulas/mathematics/college/cqegqjyagfwxjh23ubpjutxq8v43v611fz.png)
⇒ Radius = √104 = 2√26
C)- The equation of circle is determined by formula:
![(x-h)^(2)+(y - k)^(2) = r^(2)](https://img.qammunity.org/2020/formulas/mathematics/college/wf3tmyjg08qmbiqairpi4mx0pvk702ca54.png)
where (h, k ) is center of circle and
r is the radius of circle.
⇒ (x - 3)² + (y - 2)² = 104
⇒ x² + y² - 6x - 4y -91 = 0
which is the required equation of the circle.